Synthesis and non-volatile electrical memory characteristics of triphenylamine-based polyimides with flexibility segments. (5th November 2018) - Yang, Yanhua; Xia, Jing-Cheng; Zheng, Youxuan; Shen, Yingzhong; Gou, Gaozhang
Abstract : Two triphenylamine-based polyimides (PI(TPA-PMDA) andPI(TPA-BPDA) ) containing a flexibility segments were prepared. The memory device of ITO/PI(TPA-PMDA) /Al exhibited write-once read-many-times (WORM) memory behavior, however, the memory device ofPI(TPA-BPDA) demonstrated flash-type memory characteristics. Abstract : An efficient and readily available novel asymmetric diamine monomer containing a strongly electron-donating triphenylamine moiety and a flexibility segment was designed and synthesized through a Suzuki coupling reaction. Then, two thermally stable and highly soluble polyimides (PI(TPA-PMDA) andPI(TPA-BPDA) ) were prepared and characterized. The ITO/PI(TPA-PMDA) /Al memory device exhibited write-once read-many-times (WORM) memory behavior with a threshold voltage of −1.12 V, while thePI(TPA-BPDA) memory device demonstrated flash-type memory behavior with a turn-on voltage at −0.78 V and a turn-off voltage at +1.98 V. Both devices showed high ON/OFF current ratios beyond 10 3 and long retention times of 4 × 10 3 s. Space-charge limited-current (SCLC) conduction and local filament conduction governed the OFF- and ON-state current conduction of the two memory devices, respectively. The electrical memory switching behaviors were induced by a charge transfer process under an applied electric field, and the differences between the dihedral angles and dipole moments resulted in different memory types.